The Influence of Principal's Academic Supervision and Performance on The Learning Effectiveness of Senior High School Teachers - Makaudis, Jerry A.; Tambingon, Henny; Mogea, Tini (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Learning effectiveness is the relationship between the objectives and outcomes of a learning. The completion of learning outcomes indicates the achievement of the planned learning objectives so that learning is said to be effective. This study aims to determine the effect of Principal Academic Supervision and Performance on the Effectiveness of Learning of Teachers at Tondano State Senior High School, Minahasa Regency: Principal academic supervision has a significant effect on the effectiveness of learning of teachers at Tondano State Senior High School, Minahasa Regency. High School, Minahasa Regency. The population in this study were teachers at Tondano State Senior High School, Minahasa Regency with a sample of 89 teachers. The method used is regression. The data of this study were collected using a questionnaire technique and analyzed using simple and multiple regression techniques tabulated with the SPSS for Windows version 25 program. The results of the study: there is a significant influence between the principal's academic supervision on the effectiveness of teacher learning at Tondano State Senior High School, Minahasa Regency. It is recommended: The effectiveness of teacher learning at Tondano State Senior High School, Minahasa Regency needs to be improved continuously. The principal of Tondano State Senior High School, Minahasa Regency, controls good academic supervision in supporting maximum teacher performance and effectiveness of learning. can improve learning effectiveness optimally.